Mitigation of whole-body gamma radiation–induced damages by Clerodendron infortunatum in mammalian organisms. (18th November 2016) - Chacko, Tiju; Menon, Aditya; Majeed, Teeju; Nair, Sivaprabha V.; John, Nithu Sara; Nair, Cherupally Krishnan Krishnan
Abstract: Several phytoceuticals and extracts of medicinal plants are reported to mitigate deleterious effects of ionizing radiation. The potential of hydro-alcoholic extract of Clerodendron infortunatum (CIE) for providing protection to mice exposed to gamma radiation was investigated. Oral administration of CIE bestowed a survival advantage to mice exposed to lethal doses of gamma radiation. Radiation-induced depletion of the total blood count and bone marrow cellularity were prevented by treatment with CIE. Damage to the cellular DNA (as was evident from the comet assay and the micronucleus index) was also found to be decreased upon CIE administration. Radiation-induced damages to intestinal crypt cells was also reduced by CIE. Studies on gene expression in intestinal cells revealed that there was a marked increase in the Bax/Bcl-2 ratio in mice exposed to whole-body 4 Gy gamma radiation, and that administration of CIE resulted in significant lowering of this ratio, suggestive of reduction of radiation-induced apoptosis. Also, in the intestinal tissue of irradiated animals, following CIE treatment, levels of expression of the DNA repair gene Atm were found to be elevated, and there was reduction in the expression of the inflammatory Cox-2 gene. Thus, our results suggest a beneficial use of Clerodendron infortunatum for mitigating radiation toxicity.